Full Analog Broadband Time-Reversal Module for Ultra-Wideband Communication System - Zhipeng Wang; Bing-Zhong Wang; Deshuang Zhao; Ren Wang (IEEE Photonics Journal)
We built a full analog broadband time-reversal module and applied it to a prototype of ultra-wideband communication system. The time-reversal module is a temporal pulse shaping system using microwave photonic technology and it performs time-reversal operation on microwave signals based on the principle of temporal imaging. The module has an excellent time-reversal performance for microwave pulse signals and its system bandwidth exceeds 10 GHz. Based on the analog time-reversal module, a prototype of ultra-wideband communication system was established and we successfully completed the information transmission experiment to verify the feasibility of the system.